If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 11 + -1a = 2 Reorder the terms: 11 + 4a + -1a = 2 Combine like terms: 4a + -1a = 3a 11 + 3a = 2 Solving 11 + 3a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3a = 2 + -11 Combine like terms: 11 + -11 = 0 0 + 3a = 2 + -11 3a = 2 + -11 Combine like terms: 2 + -11 = -9 3a = -9 Divide each side by '3'. a = -3 Simplifying a = -3
| 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 | | 1300.46=2*3.14r^2+2*3.14*6.2 | | y=100+x+(7-x) | | y(15x-18)= | | 4x+7+3x-17=180 | | X=-16x^2+38 | | 2x-x^2=.91 | | 3b^2-4b-4= | | z^2+11z=-24 | | -5+2(1)=-4 | | x-.3x=30.80 | | 2+Y+2=10-3 | | 5x-5+x-7=180 | | (3y+5)(6y-1)= | | 4+Y=18-Y | | 1.49+a=2.99 | | 16(t-5)+5t=7(3t+3)-11 |